Analysis of Accountability and Transparency Management of Village Fund Allocations (ADD) Case Study in Muaro Panco Barat Village - Niken Hervina; Iskandar Sam; Fredy Olimsar (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine and analyze the Accountability of Village Fund Allocation Management (ADD) in Muaro Panco Barat Village AS WELL AS determine and analyze the Transparency of Village Fund Allocation Management (ADD) in Muaro Panco Barat Village. The method in this research uses a qualitative method to describe the data that has been collected as it is without the intention of drawing general conclusions. Based on the results of the research described in the previous discussion, several conclusions can be drawn, namely Based on the results that the level of accountability in the management of Village Fund Allocation (ADD) in Muaro Panco Barat Village, Renah Pembarap District, Merangin Regency is very good, where the planning, administration, reporting and accountability stages have been completed. can be implemented very well and the implementation stages are carried out well. Then the level of transparency in the management of Village Fund Allocation (ADD) in Muaro Panco Barat Village, Renah Pembarap District, Merangin Regency is very good.